ROCKETS – a novel one-for-all toolbox for light sheet microscopy in drug discovery - Mueller, Joerg P. J.; Dobosz, Michael; O’Brien, Nils; Abdoush, Nassri; Giusti, Anna Maria; Lechmann, Martin; Osl, Franz; Wolf, Ann-Katrin; Arellano-Viera, Estibaliz; Shaikh, Haroon; Sauer, Markus; Rosenwald, Andreas; et al. (Frontiers in Immunology, 2023)
Advancing novel immunotherapy strategies requires refined tools in preclinical research to thoroughly assess drug targets, biodistribution, safety, and efficacy. Light sheet fluorescence microscopy (LSFM) offers unprecedented fast volumetric ex vivo imaging of large tissue samples in high resolution. Yet, to date laborious and unstandardized tissue processing procedures have limited throughput and broader applications in immunological research. Therefore, we developed a simple and harmonized protocol for processing, clearing and imaging of all mouse organs and even entire mouse bodies. Applying this Rapid Optical Clearing Kit for Enhanced Tissue Scanning (ROCKETS) in combination with LSFM allowed us to comprehensively study the in vivo biodistribution of an antibody targeting Epithelial Cell Adhesion Molecule (EpCAM) in 3D. Quantitative high-resolution scans of whole organs did not only reveal known EpCAM expression patterns but, importantly, uncovered several new EpCAM-binding sites. We identified gustatory papillae of the tongue, choroid plexi in the brain and duodenal papillae as unexpected previously unanticipated locations of high EpCAM expression. Subsequently, we confirmed high EpCAM expression also in human tongue and duodenal specimens. Choroid plexi and duodenal papillae locations may be considered as particularly sensitive sites due to their importance for liquor production or as critical junctions draining bile and digestive pancreatic enzymes into the small bowel, respectively. These newly gained insights appear highly relevant for clinical translation of EpCAM-addressing immunotherapies. Thus, ROCKETS in combination with LSFM may help to set new standards for preclinical evaluation of immunotherapeutic strategies. Conclusively, we propose ROCKETS as an ideal platform for a broader application of LSFM in immunological research optimally suited for quantitative co-localization studies of immunotherapeutic drugs and defined cell populations in the microanatomical context of organs or even whole mice.